SEJARAH PENDIDIKAN ISLAM MASA PERTENGAHAN DI KERAJAAN USMANI, SYAFAWI, DAN MUGHAL - Muhamad Nurfahbiansyah; Nining Syamsi Komariah (TARBIYAH DARUSSALAM: JURNAL ILMIAH KEPENDIDIKAN DAN KEAGAMAAN, 2025)
The history of Islamic education is information on the development and growth of Islamic education, both in terms of concepts, ideas, institutions and operations since the time of the Prophet Muhammad. The writing of this article uses the library research method, examining reading books and then concluding the results. The history of Islamic civilization in the Middle Ages itself includes three periods of great empires, namely the Ottoman Empire in Turkey, the Safavid Empire in Persia, and the Mughal Empire in India, ruling in power. The presence of these three kingdoms reflects a shift in dominance from the dominant Arab power in classical times. Although this period is generally often considered a period of decline, the historical reality of education under the three kingdoms shows significant development and progress. Under the Ottoman Empire, madrassas were encouraged to study a wide range of sciences. During the reign of the Ottoman Empire, many educational institutions were established, one of which was the first madrassa established in Izmir in 1331 AD. Educational conditions in the Safawi Kingdom were characterized by a very strong academic atmosphere. One of the aspects is tolerance and freedom of opinion. Despite the strict indoctrination during the reign of Shah Abbas II, there was also a moment when liberal freedom of thought flourished. Meanwhile, in the Mughal Empire, education received significant attention. The government encourages mosques to function not only as places of worship, but also as centers for religious learning for the community.